2022
DOI: 10.1101/2022.05.27.493687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophila insulator proteins exhibit in-vivo liquid-liquid phase separation properties

Abstract: Mounting evidence implicates liquid-liquid phase separation (LLPS), the condensation of biomolecules into liquid-like droplets in the formation and dissolution of membraneless intracellular organelles (MLOs). Eukaryotic cells utilize MLOs or condensates for various biological processes, including emergency signaling, spatiotemporal control over steady-state biochemical reactions and heterochromatin formation. Insulator proteins function as architectural elements involved in establishing independent domains of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…The mechanism by which γH2Av interacts with Su(Hw) insulator components is still unknown. In addition to direct interactions γH2Av may also interact with insulator proteins through weak multivalent interactions [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which γH2Av interacts with Su(Hw) insulator components is still unknown. In addition to direct interactions γH2Av may also interact with insulator proteins through weak multivalent interactions [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction between the phosphorylated H2Av, but not the unphosphorylated form, with one or more gypsy insulator proteins could explain the findings presented here, both at the chromatin level and insulator bodies. Alternatively, research from our lab [ 89 ] has revealed that insulator proteins have liquid-liquid phase separation properties in vivo , which suggest the possibility that the association between γH2Av and insulator proteins may be mediated by weak multivalent interactions leading to the formation of insulator protein condensates.…”
Section: Discussionmentioning
confidence: 99%
“…For another example, although sequence-based predictions of EPIs underestimated actual interactions, an activity-by-contact (ABC) approach, based on a simple distance model, performed well, suggesting that factors in addition to sequence influence EPIs 31,32 . Furthermore, CTCF-mediated chromatin looping induces phase separation between the inner and outer regions of the loops, resulting in the formation of transcriptional condensates and insulator function [33][34][35] . Therefore, structures that result in phase separation, rather than functional differences in DBPs, may be responsible for insulator functions.…”
Section: Discussionmentioning
confidence: 99%
“…The early discovery of insulator bodies led to the proposal that insulators mediate the formation of stable, rosette-like hubs involving multiple insulator-bound genomic regions [52][53][54][55] . More recently, it was shown that CP190 and Su(HW) insulator bodies formed in cultured-cells under stress conditions exhibit liquid-liquid phase separation properties 56 . This model predicts that genomically-close insulators should interact in space often, nucleating interactions between multiple partners.…”
Section: Discussionmentioning
confidence: 99%